2013
DOI: 10.1002/pc.22722
|View full text |Cite
|
Sign up to set email alerts
|

The structure and electro‐mechanical properties of novel hybrid CNT/PANI nanocomposites

Abstract: Electrically conductive elastomeric nanocomposites containing carbon nanotubes (CNT) and polyaniline (PANI) are reported in the present investigation. The synthesis procedure included an in situ inverse emulsion polymerization of aniline doped with dodecylbenzene sulfonic acid (DBSA) in the presence of CNT and dissolved styrene‐isoprene‐styrene (SIS) block copolymer. The PANI synthesis step was carried out by applying ultrasonic energy. The dispersions obtained were processed by two methods: a recently develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Poly(styrene‐ block ‐polyisoprene‐ block ‐polystyrene) elastomer self‐assembles in methanol and causes “islands” formation during the vacuum filtration step. The self‐assembling behavior is due to the methanol being a non‐solvent . Conductive PANI/Ag particles are swept away by the SIS particles that form a continuous conductive network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(styrene‐ block ‐polyisoprene‐ block ‐polystyrene) elastomer self‐assembles in methanol and causes “islands” formation during the vacuum filtration step. The self‐assembling behavior is due to the methanol being a non‐solvent . Conductive PANI/Ag particles are swept away by the SIS particles that form a continuous conductive network.…”
Section: Resultsmentioning
confidence: 99%
“…The elastomeric “islands” display a diverse size distribution, varying from nano to the micron scale. The size of the “islands” depends on the concentration of the conductive particles and the formation process as described elsewhere . The inset below shows the magnified fragment of Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that the in situ polymerization of PANI in the presence of CNTs is found to be a good approach for the homogenized dispersion of CNTs in the reaction system . PANI wrapped the CNTs via Van der Waals interaction and π–π stacking could control its shape, electrical conductivity and make them useful in plastic electronics . On the other hand, surfactants also play an important role in the field of nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Compared with inorganic acid, organic acids containing large alkyl groups not only have high thermal stability, but also can improve the melting and solution processability of PANI. [11][12][13] Moreover, template synthesis of PANI composites is an effective method to improve the processability of PANI. A stoichiometric mixture of aniline monomer (ANI) and DBSA reacts to form a ne stable dispersion of PANI in the aqueous medium.…”
Section: Introductionmentioning
confidence: 99%